THE METHODOLOGY FOR INSTRUCTING ORAL TEXT COMPOSITION IN PRIMARY EDUCATION WITHIN THE FRAMEWORK OF MOTHER TONGUE AND READING LITERACY COURSES. - Baxronova Sarvinoz Akbar qizi; Haydarova Mahliyo Amrillo qizi (KONFERENSIYALAR, 2025)
Аnnotation. This article explores the significance of teaching methodologies for  oral text  composition in primary  school  mother  tongue  and literacy  classes, and  their  role  in  enhancing  students’  language  acquisition  and  logical  thinking skills. It examines the main methods used in teaching oral text construction, their impact  on  learners,  as  well  as  innovative  approaches  informed  by  international experience. The  article  also  provides  practical  recommendations  relevant  to  the education system in Uzbekistan.